Padronização do teste dot blotting semi-quantitativo – aplicação no diagnóstico, seguimento e recaída da paracoccidioidomicose - Pereira, Beatriz Aparecida Soares [UNESP] (2023)
Introduction. Paracoccidioidomycosis (PCM) is a systemic granulomatous disease caused by fungi of the genus Paracoccidioides. The identification of the etiologic agent in clinical specimens is the gold standard of its diagnosis. However, serological tests are also used with this objective, besides helping characterize the patient's severity and treatment follow-up. The double agar gel immunodiffusion test (DID) is considered the standard serological reaction in PCM; however, it has some limitations, such as its usual negativity in the cerebrospinal fluid, the lower sensitivity in cases of relapse, and immunosuppressed patients. Thus, the present study aimed to standardize the semi-quantitative dot blotting assay (DB) and the real-time polymerase chain reaction (RT-PCR) to detect specific antibodies for Paracoccidioides brasiliensis and its DNA in PCM patients. Methodology. We evaluated 42 confirmed PCM patients at admission (pre-treatment) using DID and DB in serum samples and RT-PCR in total blood. For assessing cross-reactions, we included 42 healthy individuals as controls and 37 patients with other infectious diseases (tuberculosis, n=10; aspergillosis, n=10; histoplasmosis, n=10; cryptococcosis, n=7). The serological progress with the treatment was evaluated in eight patients: four with the acute/subacute form (AF) and four with the chronic form (CF) of PCM. The diagnosis of relapse was evaluated in 10 patients, pairing the results observed at admission and the moment of the relapse. The culture filtrate of the yeast phase of the Pb B.339 strain was the antigen used in the 1:8 dilution. The cut-off point was determined by the receiver operator characteristic (ROC) curve for DID as much as for DB. Results. The ROC curve showed that the cut-off was the undiluted serum for both DID and DB. DB results were available in five hours, while those of DID were available in four days. RT-PCR showed lower positivity (9.5%) than the serological tests DID (73.8%) and DB (78.6%) assay. The accuracy parameters of sensitivity, specificity, positive and negative predictive values, accuracy, and positive and negative likelihood ratios were 78.6%, 100.0%, 100.0%, 82.4%, 89.3%, 330, and 0.21 for DB, and 73.8%, 100.0%, 100.0% 79.2%, 86.9%, 310, and 0.26 for DID, respectively. Cross-reactions were not observed in serum samples of patients with histoplasmosis, tuberculosis, aspergillosis, and cryptococcosis in DB. The serum levels were always higher in DB than in DID. AF patients showed regression of DID titers to non-reagent and of DB titers to non-reagent or reagent undiluted in the studied period, differently of CF patients—their DB titers persisted to reagent while DID titers decreased to non-reagent. In the diagnosis of relapse, DB showed much higher sensitivity (90%) than DID (30%). Conclusions. Our findings demonstrated that: A. in the diagnosis at admission (pre-treatment), DB and DID presented similar accuracy, but DB was easier to perform and offered earlier results, while RT-PCR in blood samples had no indication; B. cross-reactions were not observed with serum from samples of patients with tuberculosis, aspergillosis, histoplasmosis, and cryptococcosis when the antigen was used in the dilution standardized; C. DB and DID were useful in the follow-up of PCM patients under antifungal treatment; D. DB presented much higher sensitivity than DID in the diagnosis of relapse, becoming its reaction of choice; E. based on these findings, the semi-quantitative DB assay should be introduced in the clinical laboratories.